Developing a Web-Based Application for Teaching English Literature Through Interactive Reading - Rahma, Gengria Dwifani (International Journal of Research and Applied Technology (INJURATECH), 2025)
This study aims to develop a web-based application specifically designed for teaching English literature through interactive reading methods. A primary challenge in contemporary literary education is the low level of student engagement with classical texts, which are often perceived as dense and inaccessible. Utilizing a simplified Research and Development (R&D) approach in the form of a systematic literature review, this research explores the integration of digital annotation features, real-time quizzes, and gamification elements. The findings indicate that interactive platforms are capable of bridging linguistic barriers and enhancing the reader's emotional connection to the text. This abstract highlights that the application of web technology does not merely digitize text but transforms the reading experience from passive to active. The implementation of this application is expected to serve as an innovative pedagogical solution within the higher education English literature curriculum, focusing on enhancing critical literacy and fostering deeper, more engaging retention of literary content.